2017
DOI: 10.1007/s13197-017-2594-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects of certain enzymes on the rheology of dough and the quality characteristics of bread prepared from wheat meal

Abstract: This study was carried out to evaluate the effects of amyloglucosidase, glucose oxidase, hemicellulase (mainly consist of endo-1,4-b-xylanase), cellulase, lipase, and the combination of phospholipase and hemicellulase (phospholipase ? hemicellulase) on the extensographic properties of dough and the quality characteristics of bread prepared from wheat meal. The enzymes were added separately in two different amounts. The addition of glucose oxidase (at 0.0003-0.001%) caused a significant decrease in the resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
3
14
1
Order By: Relevance
“…Among the oxidants, ascorbic acid has been successfully tested (Galliard & Collins, 1988; Indrani & Rao, 1992a, 1992b). This aligns with the already mentioned positive effect of glucose oxidase (Altınel & Ünal, 2017a, 2017b), which is an oxidizing enzyme. But perhaps, the most widely used ingredient in the preparation of whole‐wheat bread, to compensate for the dilution of gluten, is vital gluten itself (Day, Augustin, Batey, & Wrigley, 2006; Indrani & Rao, 1992a; Lai, Davis, & Hoseney, 1989).…”
Section: How To Improve the Quality Of Whole‐grain Wheat Flours And Wsupporting
confidence: 91%
See 2 more Smart Citations
“…Among the oxidants, ascorbic acid has been successfully tested (Galliard & Collins, 1988; Indrani & Rao, 1992a, 1992b). This aligns with the already mentioned positive effect of glucose oxidase (Altınel & Ünal, 2017a, 2017b), which is an oxidizing enzyme. But perhaps, the most widely used ingredient in the preparation of whole‐wheat bread, to compensate for the dilution of gluten, is vital gluten itself (Day, Augustin, Batey, & Wrigley, 2006; Indrani & Rao, 1992a; Lai, Davis, & Hoseney, 1989).…”
Section: How To Improve the Quality Of Whole‐grain Wheat Flours And Wsupporting
confidence: 91%
“…For example, the use of alpha‐amylases, which allow the generation of fermentable sugars from damaged starch, helps to increase the volume and reduce the hardness of both white and whole‐wheat breads (Armero & Collar, 1996), or that of breads elaborated with mixtures of white and WWFs (Matsushita et al., 2017). Altınel and Ünal (2017a, 2017b) also reported that other enzymes, such as glucose oxidase, hemicellulose, and phospholipase + hemicellulose, can be used to improve the characteristics of dough and bread prepared from WWF. From all the enzymes, hemicellulases are the most studied enzymes to modify the components of bran with positive results, and among these, xylanases stand out (Altınel & Ünal, 2017a, 2017b; Butt, Tahir‐Nadeem, Ahmad, & Sultan, 2008; Courtin & Delcour, 2002; Driss et al., 2013; Ghoshal, Shivhare, & Banerjee, 2013; Park, Fuerst, & Baik, 2019; Shah, Shah, & Madamwar, 2006).…”
Section: How To Improve the Quality Of Whole‐grain Wheat Flours And Wmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cel and xyl have been shown to increase the volume of white pan bread (Haros et al, 2002). The present study also demonstrated increased loaf volume due to xyl, consistent with several other reports for whole wheat bread (Altinel & Ünal, 2017b;Carvalho et al, 2017;Ghoshal et al, 2013). Cel and xyl are both types of hemicellulase, a group of enzymes that hydrolyze nonstarch polysaccharides (Sluimer, 2005).…”
Section: Bread Propertiessupporting
confidence: 92%
“…not report any significant effect on dough properties or loaf volume (Altinel & Ünal, 2017b). We have previously reviewed the literature on enzymes in whole wheat dough and bread (Tebben, Shen, & Li, 2018).…”
Section: Introductionmentioning
confidence: 99%